HER-2 incidence in gastric cancer, its association with prognosis and clinicopathological parameters - (:unkn) unknown (TURKISH SURGICAL ASSOC, 2015)
Objective: Human epidermal growth factor-2 (HER-2) overexpression has prognostic value in breast cancer. However, the significance of HER-2 positivity in gastric cancer is controversial. In this study, we investigated the frequency of overexpression of HER-2 and its relationship with clinicopathological findings and impact on survival in gastric cancer. Material and Methods: Gastric cancer patients, operated in Marmara University Faculty of Medicine, Pendik Training and Research Hospital, General Surgery Department, between January 2012-December 2013 were enrolled in this study. Medical records were retrospectively evaluated. Tissue samples were stained by immunohistochemistry (IHC) method, and were followed by fluorescence in situ hybridization (FISH) in those with positive results. HER-2 expression rates and its association with other histopathological features and survival have been analyzed. Results: 135 patients were enrolled in the study, with 88 (65%) male and 47 (35%) female patients. The median age was 61 (29-84) years. Only 11 patients (8%) were positive for HER-2. HER-2 positive patients were similar to negative patients in terms of age, gender, tumor size, tumor location, tumor T stage, lymph node metastasis, histological type, differentiation, lymphovascular invasion, perinodal, perineural invasion and stage. No significant difference was detected on 1 and 2-year overall and disease-free survival rates between receptor positive and negative groups. Conclusion: Consistent with the literature data, HER-2 positivity rate in this study was approximately 8%, but this positivity has not been found to be associated with either clinical and pathological parameters or overall and disease- free survival.
Keywords: HER-2; gastric cancer; prognosis; C-ERBB-2 PROTEIN EXPRESSION; GENE AMPLIFICATION; SURVIVAL; OVEREXPRESSION; ADENOCARCINOMA; TRASTUZUMAB; RESECTION; MARKER; IMPACT